The acoustic-emissive analysis of transient operation of the friction machine. - Заспа, Ю.П.; Шалапко, Ю.І.; Возняк, А.Л. (Problems of Tribology, 2015)
Yu.P. Zaspa, Yu.I. Shalapko, A.L. Voznyak. The acoustic-emissive analysis of transient operation of the fric-tion machine. The transitional modes of experimental friction machine are investigated by the method of the spectral analysis of the acoustic emission. Significant differences between such modes and the established modes of the operation of the machine – both as for the spectral composition of the vibroacoustic field and the direction of the cascade energy transfer processes in a dynamic system were revealed. The maximum level of the inertial loads in the starting modes of the machine and mecha-nisms that creates the risk of accidents was marked.